2012
DOI: 10.1016/j.cct.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and potential solutions to meeting accrual goals in a Phase II chemoprevention trial for prostate cancer

Abstract: Objective The goal of this report is to describe the on going strategies, successes, challenges and solutions for recruitment in this multi-center, phase II chemoprevention trial targeting men at high risk for prostate cancer. Methods We developed and implemented a multi-center clinical trial in institutions with supportive infrastructure, lead by a recruitment team of experienced and committed physicians and clinical trial staff, implementing multi-media and community outreach strategies to meet recruitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 18 publications
3
16
1
Order By: Relevance
“…Randomized chemoprevention trials using agents similar to readily available over-the-counter supplements present unique challenges to recruitment and retention (63). Although several infrastructure, protocol-related and personal factors were taken into consideration while designing the clinical trial, safety monitoring imposed by the FDA continued to challenge recruitment and retention.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized chemoprevention trials using agents similar to readily available over-the-counter supplements present unique challenges to recruitment and retention (63). Although several infrastructure, protocol-related and personal factors were taken into consideration while designing the clinical trial, safety monitoring imposed by the FDA continued to challenge recruitment and retention.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges are significantly associated with protocol and patient-related factors, including the behavioral dynamics of the research team, institutional infrastructure, community and participating subjects [14]. Although other research teams [8,16] have examined feasibility of strategies used to recruit former smokers in chemoprevention trials, these strategies remain costly, not targeted to specific populations nor contemporary. Once the target population, the source of subjects and agent to be evaluated have been identified, it is critical for research teams to carefully examine the potential challenges and facilitators unique to the target population, study agent and disease site as a first step of the design phase of a lung cancer chemoprevention trial.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike other trials with experimental drugs or vitamins and minerals, chemoprevention trials using botanicals present unique challenges to recruitment 12. We and others have observed several barriers to recruitment in chemoprevention trials using botanicals including research environment, protocol and subject related factors [16]. Although institutional databases, mass media and community outreach efforts to recruit participation in clinical trials have demonstrated success in epidemiological studies and treatment trials, we have not experienced the same success in recruitment to early phase trials with FDA approved botanicals [14,15].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although several early clinical trials have been initiated using Polyphenon E, including our clinical trial in progress, based on the available data from preclinical studies, restrictions to eligibility imposed by the FDA continue to place a significant challenge on recruitment of subjects to these trials. (5, 51)…”
Section: Introductionmentioning
confidence: 99%